Blue LED causes autophagic cell death in human osteosarcoma by increasing ROS generation and dephosphorylating EGFR. Issue 11 (7th May 2021) - He, Mingyu; Yan, Gege; Wang, Yang; Gong, Rui; Lei, Hong; Yu, Shuting; He, Xiaoqi; Li, Guanghui; Du, Weijie; Ma, Tianshuai; Gao, Manqi; Yu, Meixi; et al.
Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumour in adolescence. Lately, light‐emitting diodes (LED)‐based therapy has emerged as a new promising approach for several diseases. However, it remains unknown in human OS. Here, we found that the blue LED irradiation significantly suppressed the proliferation, migration and invasion of human OS cells, while we observed blue LED irradiation increased ROS production through increased NADPH oxidase enzymes NOX2 and NOX4, as well as decreased Catalase (CAT) expression levels. Furthermore, we revealed blue LED irradiation‐induced autophagy characterized by alterations in autophagy protein markers including Beclin‐1, LC3‐II/LC3‐I and P62. Moreover, we demonstrated an enhanced autophagic flux. The blockage of autophagy displayed a remarkable attenuation of anti‐tumour activities of blue LED irradiation. Next, ROS scavenger N‐acetyl‐L‐cysteine (NAC) and NOX inhibitor diphenyleneiodonium (DPI) blocked suppression of OS cell growth, indicating that ROS accumulation might play an essential role in blue LED‐induced autophagic OS cell death. Additionally, we observed blue LED irradiation decreased EGFR activation (phosphorylation), which in turn led to Beclin‐1 release and subsequent autophagy activation in OS cells. Analysis of EGFR colocalization with Beclin‐1 and EGFR‐immunoprecipitation (IP) assay further revealed the decreased interaction of EGFR and Beclin‐1 upon blue LED irradiation in OS cells. In addition, Beclin‐1 down‐regulation abolished the effects of blue LED irradiation on OS cells. Collectively, we concluded that blue LED irradiation exhibited anti‐tumour effects on OS by triggering ROS and EGFR/Beclin‐1‐mediated autophagy signalling pathway, representing a potential approach for human OS treatment.